The Phenomenon of Cognitive Anxiety in Learning Islamic Education Subjects - Atikah Argi; Wildan Shohib, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The obligation to undergo tahsin and tahfidz and learn Arabic in Islamic schools is a frightening specter for some students, causing a phenomenon in the form of cognitive anxiety every time they undergo Islamic religion lessons. This study uses a qualitative literature research approach and phenomenology, where researchers try to understand the phenomena that occur and develop. This research aims to explain the essential points that can add to the readiness of knowledge from educational institutions in preparing learning methods and mental students to be ready to plunge into social life. This study's results indicate that optimizing the factors described can foster positive results by 1) gaining public trust, 2) developing learning methods, 3) improving student achievement, and 4) student achievement in academic and non-academic fields.